Using concept maps to understand mechanical physics concepts in high school students (2020)
The work presents a didactic proposal on the use of concept maps, for the understanding of mechanical physics. A didactic intervention based on Ausubel's theory was applied with the following activities: design, implementation and application of workshops based on real physical situations, where the elaboration of concept maps is the central axis, under the quantitative paradigm of interpretative level and action research method. The informants were 43 tenth grade students from a public educational institution located in the Department of Norte de Santander, Colombia. The results obtained showed that the use of concept maps as a didactic intervention favoured the significant learning of classical mechanics concepts. It was evident that the participating students achieved reflective analysis about the resolution of problems about the concepts of mechanics.